2015
DOI: 10.1097/cmr.0000000000000140
|View full text |Cite
|
Sign up to set email alerts
|

Let-7b overexpression leads to increased radiosensitivity of uveal melanoma cells

Abstract: Uveal melanoma (UM) is an intraocular malignant tumor in adults that is characterized by rapid progression and recurrence. Irradiation has become the primary therapy for UM patients who are not candidates for surgery. However, after large-dose fraction irradiation treatment, some patients undergo subsequent enucleation because of radiotherapy-related complications. This situation has raised concerns on how to optimize the effectiveness of radiation treatment. Recent investigations of microRNAs are changing our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Let-7 has also been demonstrated as a strong discriminator in primary UM, and has been reported at low levels in OCM1 cells 11, 20. Research indicates that let-7b over-expression down-regulates cyclin D1 expression, which plays a critical role in cell cycle arrest, and enhances the radio-sensitivity of UM through cell cycle arrest 21.…”
Section: Epigenetic Mechanisms In Ummentioning
confidence: 99%
See 1 more Smart Citation
“…Let-7 has also been demonstrated as a strong discriminator in primary UM, and has been reported at low levels in OCM1 cells 11, 20. Research indicates that let-7b over-expression down-regulates cyclin D1 expression, which plays a critical role in cell cycle arrest, and enhances the radio-sensitivity of UM through cell cycle arrest 21.…”
Section: Epigenetic Mechanisms In Ummentioning
confidence: 99%
“…Zhou et al . found that let-7b could potentially be used as a radio-sensitivity enhancer in UM radiotherapy 21. miR-34b/c expression, which is dramatically reduced in UM cells and clinical samples, can be up-regulated by doxorubicin and epigenetic drugs.…”
Section: Potential Therapeutics Targeting Epigenetic Regulatorsmentioning
confidence: 99%
“…Other data indicate an association of the let-7 family with outcome of chemo and radiotherapy. In uveal melanoma, high expression of let-7g has been associated with better outcome of chemo- or radiotherapy [ 27 ]. The up-regulation of let-7g-5p has also been correlated with improved PFS and OS in patients with ovarian cancer receiving neoadjuvant chemotherapy [ 28 ] and similar data is reported in rectal cancer for high expression of let-7g [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was identified that the miRNA profiles are significantly different in pre-and post-irradiated cells at 5 days in multiple melanoma cell lines and suggested that miRNAs with differential expression may be associated with resistance to IR. The study led to the development of research on sensitizing melanoma to IR via miRNAs, and miR-21 and let-7b were identified as important factors in response to IR in melanoma (7,8). Therefore, it is conceivable that more miRNAs may be involved in regulating the cellular sensitivity to IR in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested an important role for miRNAs in the mediation of tumor cell sensitivity to ionizing radiation (IR) by efficiently influencing DNA damage repair, cell cycle checkpoints, apoptosis, radio-related signal transduction pathways and the tumor microenvironment (6). In melanoma, miRNA 21 (miR-21) and miR-let-7b have been demonstrated to be related to the cellular radioresistance (7,8). However, the underlying molecular mechanisms by which miRNAs regulate cellular sensitivity to IR remain unclear.…”
Section: Introductionmentioning
confidence: 99%